Kształtowanie tożsamości matki u kobiet doświadczających nieplanowanego macierzyństwa - Koronkiewicz, Kaja (Kultura-Społeczeństwo-Edukacja, 2014)
Recent years show a noticeable increase in the number of systematic scientific studies about motherhood. Mostly, the birth of a child is depicted as a groundbreaking event, carefully planned in the biography of a woman. The future mother has many doubts, usually feels joy and satisfaction of the “blessed state”. Still very few publications touch the issue of women experiencing unwanted motherhood. In widely available articles about family, unplanned pregnancy theme is limited. Mostly apply to youngsters. This phenomenon, regardless of age, is a critical event in a woman's life. It should therefore become a research exploration area of educators and representatives of related disciplines. The article attempts to depict the situation of mothers facing unplanned parenthood. Heroines present experiences related to pregnancy, birth and childcare. Fragments of their biographies show both their concerns and moments full of joy and pride.